2019
DOI: 10.5505/ejm.2019.50455
|View full text |Cite
|
Sign up to set email alerts
|

Simple Peripheral Markers for Inflammation in Drug-Naive, Comorbidity-Free Adolescents with Obsessive–Compulsive Disorder

Abstract: Obsessive-compulsive disorder (OCD) is a neuropsychiatric disorder with recurrent obsessions and/or compulsions that cause distress, time-consuming and/or significant disruption (1). The prevalence of OCD is %1-3 (2). OCD is divided into 2 groups according to the age of onset; early onset (12-14 years) and late onset (20-22 years) (3,4). Childhood-onset OCD is suggested to be distinguished with late-onset OCD by different etiopathogenic mechanisms (4,5). The pathophysiology of OCD is still unknown, recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Ozyurt and Binici (2019) reported significantly higher total WBC and neutrophil levels among individuals with OCD. Contrastingly, Uçar et al (2019) and Ayaydin et al (2016) found no significant differences in total WBC and neutrophil levels. Uçar et al (2019) reported significantly lower lymphocyte levels among individuals with OCD, whereas Ayaydin et al (2016) and Ozyurt and Binici (2019) did not find any significant differences.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Ozyurt and Binici (2019) reported significantly higher total WBC and neutrophil levels among individuals with OCD. Contrastingly, Uçar et al (2019) and Ayaydin et al (2016) found no significant differences in total WBC and neutrophil levels. Uçar et al (2019) reported significantly lower lymphocyte levels among individuals with OCD, whereas Ayaydin et al (2016) and Ozyurt and Binici (2019) did not find any significant differences.…”
Section: Discussionmentioning
confidence: 84%
“…Contrastingly, Uçar et al (2019) and Ayaydin et al (2016) found no significant differences in total WBC and neutrophil levels. Uçar et al (2019) reported significantly lower lymphocyte levels among individuals with OCD, whereas Ayaydin et al (2016) and Ozyurt and Binici (2019) did not find any significant differences. Ozyurt and Binici (2019) included a sample of participants with co‐morbid anxiety disorders, specifically GAD, social anxiety disorder and specific phobia and reported higher inflammation among individuals with co‐morbidities.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations